Organic chemistry - McMurry, John. (Boston, MA Cengage Learning, 2016)
The most trusted and best-selling text for organic chemistry just got better! Updated with more coverage of nuclear magnetic resonance spectroscopy, expanded with new end-of-chapter mechanism problems and Practice Your Scientific Reasoning and Analysis questions, and enhanced with OWLv2, the latest version of the leading online homework and learning system for chemistry, John McMurry's ORGANIC CHEMISTRY continues to set the standard for the course. The Ninth Edition also retains McMurry's hallmark qualities: comprehensive, authoritative, and clear. McMurry has developed a reputation for crafting precise and accessible texts that speak to the needs of instructors and students. More than a million students worldwide from a full range of universities have mastered organic chemistry through his trademark style, while instructors at hundreds of colleges and universities have praised his approach time and time again. -- Source other than Library of Congress.
Structure and Bonding -- Polar Covalent Bonds; Acids and Bases -- Organic Compounds: Alkanes and Their Stereochemistry -- Organic Compounds: Cycloalkanes and Their Stereochemistry -- Stereochemistry at Tetrahedral Centers -- An Overview of Organic Reactions -- Practice Your Scientific Analysis and Reasoning I: The Chiral Drug Thalidomide -- Alkenes: Structure and Reactivity -- Alkenes: Reactions and Synthesis -- Alkynes: An Introduction to Organic Synthesis -- Organohalides -- Reactions of Alkyl Halides: Nucleophilic Substitutions and Eliminations -- Practice Your Scientific Analysis and Reasoning II: From Mustard Gas to Alkylating Anticancer Drugs -- Structure Determination: Mass Spectrometry and Infrared Spectroscopy -- Structure Determination: Nuclear Magnetic Resonance Spectroscopy -- Conjugated Compounds and Ultraviolet Spectroscopy -- Practice Your Scientific Analysis and Reasoning III: Photodynamic Therapy (PDT) -- Benzene and Aromaticity -- Chemistry of Benzene: Electrophilic Aromatic Substitution -- Alcohols and Phenols -- Ethers and Epoxides; Thiols and Sulfides -- Preview of Carbonyl Chemistry -- Aldehydes and Ketones: Nucleophilic Addition Reactions -- Practice Your Scientific Analysis and Reasoning IV: SSRIs -- Carboxylic Acids and Nitriles -- Carboxylic Acid Derivatives: Nucleophilic Acyl Substitution Reactions -- Carbonyl Alpha-Substitution Reactions -- Carbonyl Condensation Reactions -- Practice Your Scientific Analysis and Reasoning V: Thymine in DNA -- Amines and Heterocycles -- Biomolecules: Carbohydrates -- Biomolecules: Amino Acids, Peptides, and Proteins -- Biomolecules: Lipids -- Practice Your Scientific Analysis and Reasoning VI: Melatonin and Serotonin -- Biomolecules: Nucleic Acids -- The Organic Chemistry of Metabolic Pathways -- Orbitals and Organic Chemistry: Pericyclic Reactions -- Practice your scientific analysis and reasoning VII: the potent antibiotic traits of endiandric Acid C -- Synthetic Polymers.
Includes index.
Gluztavelle Judeen Mercado (Recommending faculty) - Bookfair2017
Keywords: Chemistry, Organic -- Textbooks